Imaging Flow Cytometry and Confocal Immunofluorescence Microscopy of Virus-Host Cell Interactions - McClelland, Ryley D.; Culp, Tyce N.; Marchant, David J. (Frontiers in Cellular and Infection Microbiology, 2021)
Viruses are diverse pathogens that use host factors to enter cells and cause disease. Imaging the entry and replication phases of viruses and their interactions with host factors is key to fully understanding viral infections and their host interactions. This review will discuss how confocal microscopy and imaging flow cytometry are used to investigate virus entry and replication mechanisms and track viruses in live cells. Quantification of viral images and the use of cryo-electron microscopy to gather structural information of viruses is also explored. Using imaging to understand how viruses replicate and interact with host factors, we gain insight into cellular processes and identify novel targets to develop antiviral drugs and vaccines.